Kolaborasi Makeup Wajah Fantasi "Cruella de Vil" dan Makeup Dekoratif Pengantin Sunda Putri untuk Pesta Malam Halloween - Haen Muhaemanurrohmah; Eman, Astuti (Jurnal Tata Rias, 2023)
Facial makeup can be made according to the desired theme. Combining fantasy facial makeup with decorative makeup can create a new look. Cruella De Vil's makeup features an antagonistic character with black eyeshadow using the foxy eyes technique and black eyebrows that rise sharply. Sundanese princess bridal makeup has an elegant and calm impression, shown by green eyeshadow. Betel is the icon of this makeup look. This study aims to present a new alternative makeup look for Halloween night parties by combining Cruella's fantasy makeup with Sundanese princess bridal decorative makeup. Halloween night parties are attended by people in cosplay (Costume Play) attire. The method used is direct experimentation by the author. To achieve this new alternative makeup look, the steps include cleansing the face, preparing the skin, shaping eyebrows, applying foundation, applying eyeshadow, installing betel, applying false eyelashes, and using lipstick. From the research that has been done, it can be concluded that collaborating with 2 contrasting characters can produce a new alternative makeup look.